2008
DOI: 10.1038/ni.1686
|View full text |Cite
|
Sign up to set email alerts
|

Fc receptor γ-chain, a constitutive component of the IL-3 receptor, is required for IL-3-induced IL-4 production in basophils

Abstract: The Fc receptor common γ-chain (FcRγ) is a widely expressed adaptor bearing an immunoreceptor tyrosine-based activation motif (ITAM) that transduces activation signals from various immunoreceptors. We found here that basophils lacking FcRγ developed normally and proliferated efficiently in response to interleukin 3 (IL-3), but were severely impaired in IL-3-induced IL-4 production and in supporting T helper 2 cell differentiation. Through the transmembrane portion, FcRγ associated constitutively with the commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 49 publications
4
88
2
1
Order By: Relevance
“…It has been suggested that isotype-switched antibodies and FcRγ expression play a role in supporting Heligmosomoides polygyrus-induced expansion of basophils (44). This and other studies suggest that expression of FcRγ plays an instrumental role in basophil responses (24), and here we suggest an additional role for FcRγ that is independent of antibody binding.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…It has been suggested that isotype-switched antibodies and FcRγ expression play a role in supporting Heligmosomoides polygyrus-induced expansion of basophils (44). This and other studies suggest that expression of FcRγ plays an instrumental role in basophil responses (24), and here we suggest an additional role for FcRγ that is independent of antibody binding.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, the response to papain was enhanced in the cells that were transduced with the mutant that disrupts interaction with the FceRI α-chain (L21A) but was lost in cells transduced with the mutant that disrupts interaction with both FceRI α-chain and IL-3R βc and presumably other transmembrane receptors (D11A). This enhanced signaling in response to papain with the L21A mutant is similar to that seen in response to IL-3, perhaps suggesting that when the FceRI α-chain is not expressed a greater proportion of the pool of FcRγ is free to bind other receptors, including the IL-3R βc (24). The response to papain also required an intact ITAM domain, suggesting that papain does require activation of the ITAM signaling pathway downstream of FcRγ, but, in contrast to IgE, does not require the interaction of FcRγ with the FceRI complex.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Basophils from FcR␥-chain Ϫ/Ϫ mice were determined by their expression of CD49b and CD123 instead of CD49b and Fc RI, as previously reported. 32 We first confirmed that BMBAs differentiated normally even in the absence of the FcR␥-chain ( Figure 1E). The PGD2 and PGE2 secretion observed from BMBAs of wild-type C57BL/6 mice was completely abrogated in BMBAs of FcR␥-chain Ϫ/Ϫ mice (Figure 1, F and G).…”
Section: Fc Ri Is Involved In Ige-mediated Pgd2/e2 Secretionsupporting
confidence: 60%